Theoretical Studies Aimed at Finding FLT3 Inhibitors and a Promising Compound and Molecular Pattern with Dual Aurora B/FLT3 Activity - Fernandes, Ítalo Antônio; Braga Resende, Déborah; Ramalho, Teodorico Castro; Kuca, Kamil; da Cunha, Elaine Fontes Ferreira (Molecules, 2020)
FLT3 and dual Aurora B/FLT3 inhibitors have shown relevance in the search for promising new anticancer compounds, mainly for acute myeloid leukemia (AML). This study was designed to investigate the interactions between human FLT3 in the kinase domain with several indolin-2-one derivatives, structurally similar to Sunitinib. Molegro Virtual Docker (MVD) software was utilized in docking analyses. The predicted model of the training group, considering nineteen amino acid residues, performed in Chemoface, achieved an R2 of 0.82, suggesting that the binding conformations of the ligands with FLT3 are reasonable, and the data can be used to predict the interaction energy of other FLT3 inhibitors with similar molecular patterns. The MolDock Score for energy for compound 1 showed more stable interaction energy (-233.25 kcal mol-1) than the other inhibitors studied, while Sunitinib presented as one of the least stable (-160.94 kcal mol-1). Compounds IAF70, IAF72, IAF75, IAF80, IAF84, and IAF88 can be highlighted as promising derivatives for synthesis and biological evaluation against FLT3. Furthermore, IAF79 can be considered to be a promising dual Aurora B/FLT3 inhibitor, and its molecular pattern can be exploited synthetically to search for new indolin-2-one derivatives that may become drugs used in the treatment of cancers, including AML.
Keywords: aktivace enzymů; Aurora Kinase B; molekulární konformace; teoretické modely; inhibitory proteinkinas; Inhibitory Concentration 50; Enzyme Activation; Molecular Structure; Structure-Activity Relationship; lidé; inhibiční koncentrace 50; Molecular Conformation; Algorithms; Models, Molecular; molekulární struktura; molekulární modely; Protein Kinase Inhibitors; tyrosinkinasa 3 podobná fms; algoritmy; aurora kinasa B; vztahy mezi strukturou a aktivitou; fms-Like Tyrosine Kinase 3; Models, Theoretical; Humans